Klebsiella pneumoniae SnebYK Mediates Resistance Against Heterodera glycines and Promotes Soybean Growth - Liu, Dan; Chen, Le; Zhu, Xiaofeng; Wang, Yuanyuan; Xuan, Yuanhu; Liu, Xiaoyu; Chen, Lijie; Duan, Yuxi (Frontiers in Microbiology, 2018)
Soybean is an important economic crop that is often adversely affected by infection with the soybean cyst nematode Heterodera glycines in the field. Biological control is an eco-friendly approach to protecting the crop against disease. The bacterium Klebsiella pneumoniae has been reported to protect rice from sheath blight and seedling blight, but its role in the control of nematodes is unclear. In this study, the effect of K. pneumoniae SnebYK on controlling H. glycines was assessed. Potting experiments showed that coating soybean seeds with K. pneumoniae SnebYK not only reduced the infection rate of H. glycines but also decreased the proportion of adult female nematodes. Field experiment results indicated that K. pneumoniae SnebYK reduced both the number of H. glycines in soybean roots and the number of adult females. However, K. pneumoniae SnebYK caused low juvenile mortality in an in vitro assay. To further analyze the role of K. pneumoniae SnebYK in the inhibition of H. glycines infection, split root experiments were conducted. The results indicated that K. pneumoniae SnebYK controls H. glycines via induced systemic resistance, which caused a reduction in H. glycines penetration. Klebsiella pneumoniae SnebYK treatment also significantly increased the proportion of second-stage juvenile nematodes and decreased the proportions of third- and fourth-stage juveniles. Moreover, 48 hours after inoculation with H. glycines, the expression levels of PR1, PR2, PR5, and PDF1.2 were significantly higher in soybeans pretreated with K. pneumoniae SnebYK than in control soybeans. Interestingly, besides providing protection against nematodes, K. pneumoniae SnebYK fixed nitrogen, produced ammonia, solubilized phosphate, and produced siderophores, leading to well-developed root systems and an increase in the fresh weight of the soybean seedlings. These results demonstrate for the first time that K. pneumoniae SnebYK not only promotes the growth of soybean but also inhibits the invasion and development of H. glycines by inducing systemic resistance.